Assessment of Maternal Knowledge, Attitude, and Practice regarding Nutrition of Children Aged 12-36 Months and Its Related Factors in Qom Province, Iran, Using a Self-report Method - Mohammad Mahdi Akbari Aleagha; Siamak Mohebbi; Mohammad Aghaali; Mohammad Hozoori (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2020)
Background and Objectives: Nutrition is the first and most important factor facilitating mother-child interaction. Maternal nutritional knowledge, attitude, and practice are effective in many stages of child growth and development. Therefore, the present study was aimed to investigate the knowledge, attitude, and practice of the mothers of 12 to 36-month-old infants regarding child nutrition and its related factors using self-report method, in Qom, Iran.